Post-carbon inclusion transitions built on justice - Horne, Ralph 1966-; Ambrose, Aimee; Walker, Gordon; Nelson, Anitra 1952- (Bristol University Press, 2024)
This collection pays unique attention to the highly challenging problems of addressing inequality within decarbonisation--particularly under-explored aspects, such as high consumption, degrowth approaches and perverse outcomes. Contributors point out means and possibilities of the transition from high carbon inequalities to post-carbon inclusion. They apply a variety of conceptual and methodological approaches in all-inclusive ways to diverse challenges, such as urban heating and retrofitting. Richly illustrated with case studies from the city to the household, this book critically examines 'just transitions' to achieve sustainable societies in the future
Includes bibliographical references and index
Keywords: Carbon dioxide mitigation; Carbon dioxide mitigation / Social aspects; Sustainability; Gaz carbonique - Réduction; Durabilité de l'environnement; Gaz carbonique - Réduction - Aspect social; History